18. Laser evoked potentials and quantitative sensory testing in patients affected by multiple sclerosis: Clinical, neurophysiological and psychophysiological correlates. Issue 4 (April 2016) - Turri, M.; Donato, F.; Zanette, G.; Teatini, F.; Tugnoli, V.; Deotto, L.; Moretto, G.; Squintani, G.
Abstract : Pain is a common finding in patients affected by Multiple Sclerosis (MS). Many different types of pain can afflict MS patients, including neuropathic, nociceptive, or mixed pain. TSA-II-Thermotest (QST) and Laser evoked potentials (LEPs) are psychophysical and neurophysiological tests commonly used to explore pain. The study aims to determine psychophysical and neurophysiological correlates in MS patients. 16 MS patients (5 men, 11 women, mean age 59 years, mean EDSS 7) where clinically and neurophysiologically tested. 5 patients presented neuropathic central pain (according to NeuPSIG 2011 guidelines), 8 patients presented nociceptive or mixed pain, and 3 patients were pain-free. For QST, the dorsum of both hands and feet were examined; for LEPs, the dominant hand and both feet were tested. Results were collected and compared to age and sex matched controls. Pin-prick was altered in 37.5%, LEPs were abnormal in 57.8% and QST was pathological in 85.9% of examined sites. We detected a significant correlation between pain and clinical examination (0.022), pain and altered QST (0.042), while LEP abnormalities correlated well with the presence of neuropathic pain (0.012). Our results suggest that LEPs are more specific than QST to differentiate neuropathic from nociceptive pain.